2023
DOI: 10.7759/cureus.36972
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Ramadan Fasting in the Setting of Gastrointestinal Disorders

Abstract: Intermittent fasting is an increasingly popular dieting technique with many well-studied benefits, such as permitting weight loss in obese patients, lowering low-density lipoprotein cholesterol (LDL-C) levels and triglyceride levels, and optimizing circadian rhythms. A special type of intermittent fasting occurs during Ramadan, when Muslims worldwide fast daily from dawn to sunset for a month. Ramadan fasting has demonstrated several health benefits, including improving the gut microbiome, modifying gut hormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 54 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…Patients suffering from gastroesophageal reflux disease may benefit from fasting as studies have indicated reductions in symptoms, even when accounting for change in meal size and tobacco use. 10 , 37 , 38 Studies using upper endoscopy surveillance during Ramadan did not detect any worsening occurrences of gastritis, gastric ulcers, or gastric bleeding though there were increases in rates of duodenal ulcers and duodenitis. Patients with known duodenal disease should take caution with fasting.…”
Section: Gastrointestinal Diseasementioning
confidence: 92%
See 3 more Smart Citations
“…Patients suffering from gastroesophageal reflux disease may benefit from fasting as studies have indicated reductions in symptoms, even when accounting for change in meal size and tobacco use. 10 , 37 , 38 Studies using upper endoscopy surveillance during Ramadan did not detect any worsening occurrences of gastritis, gastric ulcers, or gastric bleeding though there were increases in rates of duodenal ulcers and duodenitis. Patients with known duodenal disease should take caution with fasting.…”
Section: Gastrointestinal Diseasementioning
confidence: 92%
“…Decreases in GLP-1 and the improved leptin/adiponectin ratio in time-restricted fasting favor decreased insulin resistance. 9 , 10 These markers are also affected by circadian rhythm, which changes during Ramadan fasting. 9 Low-density lipoprotein, triglycerides, insulin, CRP levels, and endothelial function demonstrate improvement in studies comparing periods before and during Ramadan.…”
Section: Physiologic Changes During Fastingmentioning
confidence: 99%
See 2 more Smart Citations